Managing a corporate network with time delay control information - Нагурный, А. А. (Problems of Informatization and Management, 2010)
The task of management corporate networks is considered at presence of casual delays at delivery to alarm and managing information, indignations and noises of different character. It is indicated that authenticity of recognition of class of indignation as a stationary эргодического process is the function of dispersion of estimation of cross-correlation function. Shown out expression for the estimation of possible delay of information at which control system works with efficiency not below set